Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

The Decade show: frameworks of identity in the 1980s - Young, Louis; New Museum of Contemporary Art (New York, N.Y.); Studio Museum in Harlem; Museum of Contemporary Hispanic Art (New York, N.Y.) (Museum of Contemporary Hispanic Art, 1990)
The Decade Show is a provocative examination of artistic production in the 1980s, embracing 113 artists and artists’ groups (including Ida Applebroog, Luis Cruz Azaceta, Gran Fury, Edgar Heap-Of-Birds, Komar & Melamid, Adrian Piper and Shu Lea Cheang) who - whether visible or invisible in the mainstream - are critical to an understanding of the period. Fourteen essayists, among them David Deitcher, Thelma Golden, Julia P. Herzberg, Micki McGee, Sharon F. Patton, Susan Quist and Lowery Stokes Sims, contribute to this extensive survey. As a collaborative effort between the Museum of Contemporary Hispanic Art, The New Museum and The Studio Museum in Harlem, The Decade Show reflects true community diversity, as well as the museum’s interest in examining “parallel cultures” obscured by traditional aesthetics. “This is not a patronizing exhibit of the art of ‘exotica’ put together by the philanthoropic goodwill and high-art-world curiosity of a few white curators. It is an exhibit attempting to construct a multivocal art world. It begins to suggest that the notion of a ‘center’ and a ‘margin’ is anachronistic and that maintaining such a model represents a desire to wield exclusive power and control.” -Eunice Lipton, “Here Today, Gone Tomorrow,” p. 20.
Keywords: amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; intersectionnalité; point de vue situé; premier cycle; queer; régions géographiques; états-unis